Razvoj identifikacijskega sistema za zemljišča v Sloveniji - Rotter, Alenka (Geodetski vestnik, 2011)
Although the land parcel identification system in Slovenia was established only few years ago, it has already had been changed many times. At first, an alphanumeric land cadastre data was used, then (as a graphical basis) a digital cadastral index map was introduced; however, such solutions did not meet the high quality requirements of spatial data. It had to be started againand all agricultural parcels of individual agricultural holdings were defined on the basis of digitised orthophotos. At present, the system that is represented with graphical units of agricultural parcels (GERK) has grown intoa system related to or using a broad collection of spatial data, includingregisters of permanent crops. This spatial data is used for the assurance of the required quality in procedures of maintenance and in regular procedures of administrative controls in the framework of agricultural policy.Every year, a part of the data is checked on the field. Proactive quality assurance and continuous control are the highest priority tasks. The objective is a more efficient system and a consequent reduction of risk in thedistribution of public funds to the entitled farmers. Another step forward was made in Spain, where cooperation between land cadastre and SIGPAC in the frame of the INSPIRE directive is an example of good practise, which could become a model for the other Member States.
Keywords: agricultural policy; geografski informacijski sistemi; geographic information systems; kmetijska politika; quality assurance; zagotavljanje kakovosti